2015
DOI: 10.1186/s12937-015-0085-1
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial effects of a polyphenolic grape extract (PGE) supplement on appetite and food intake: a randomised dose-comparison trial

Abstract: BackgroundThere is recent evidence that glucose delivered to the distal small intestine (SI) may stimulate the ileal brake and inhibit appetite. High polyphenolic grape extract (PGE) has been shown to inhibit α-amylase and α-glucosidase activity, two key enzymes required for starch digestion, in vitro. It is hypothesised to slow digestion and absorption of starch in the proximal SI such that glucose may be delivered distally into the ileum and suppress appetite. This study investigated the safety and efficacy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
1
5
1
Order By: Relevance
“…Importantly, studies demonstrating effects of polyphenol-rich foods on GLP-1 and/or ghrelin in a direction that would be expected to suppress appetite could not separate effects of polyphenols from the fibre and viscosity of the test meals (14,45) , which are both factors also thought to influence appetitemediating hormone responses (50) . In addition, a recent study found no acute effect of consuming 0•5-1•5 g of polyphenolrich grape seed extract on appetite (51) , despite the extract having been shown to inhibit α-amylase and α-glucosidase in vitro (52) , similar to the polyphenols used in the present study. Collectively, these findings do not support an appetite suppressing effect of berry polyphenols within the doses studied when fibre intake and viscosity are matched across fortified and non-fortified food products.…”
Section: Discussionsupporting
confidence: 47%
“…Importantly, studies demonstrating effects of polyphenol-rich foods on GLP-1 and/or ghrelin in a direction that would be expected to suppress appetite could not separate effects of polyphenols from the fibre and viscosity of the test meals (14,45) , which are both factors also thought to influence appetitemediating hormone responses (50) . In addition, a recent study found no acute effect of consuming 0•5-1•5 g of polyphenolrich grape seed extract on appetite (51) , despite the extract having been shown to inhibit α-amylase and α-glucosidase in vitro (52) , similar to the polyphenols used in the present study. Collectively, these findings do not support an appetite suppressing effect of berry polyphenols within the doses studied when fibre intake and viscosity are matched across fortified and non-fortified food products.…”
Section: Discussionsupporting
confidence: 47%
“…Out of 32 analyzed studies, 16 (50%) did not report adverse events at all. In 10 of the remaining 16 trials, none of the tested plant extracts caused an adverse event [15,48,49,54,56,64,68,70,71,76]. Six studies [51,58,63,66,67,74] reported mild adverse events such as gastrointestinal distress (e.g., dyspepsia, flatulence, diarrhea, or constipation), skin rash, or headache.…”
Section: Resultsmentioning
confidence: 99%
“…In multiple studies that recorded the outcomes over several hours on just one or two days, respectively, participants were instructed to refrain from exercise 24 to 48 h before test day [28,51,60,61,62,65,75] and to arrive after an overnight fast at the test center [52,57,62,69,70,76,86]. The bioactive phytochemical was mostly taken with a standardized meal, varying from a breakfast meal with approximately 1150 kJ (275 kcal) [73] to a breakfast buffet with a total amount of approximately 32,962 kJ (7878 kcal) [61].…”
Section: Resultsmentioning
confidence: 99%
“…We demonstrated that appetite score changed negligibly in the GSE group in comparison to the baseline (~1%), although we did not find any significant differences between the two groups which is in line with previous studies. Shin et al indicated that high polyphenolic grape extract did not alter postprandial hunger or fullness in non‐obese subjects (Shin et al, ). In addition, Vogels et al observed that 300 mg grape‐seed extract (polyphenolics) containing 90% procyanidines can reduce 24‐hr energy intake by 4% while no effects on satiety was observed in normal and overweight individuals (Vogels et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, polyphenols have beneficial effects against obesity through modulating inflammatory markers (Corrêa & Rogero, ) and grape components have been introduced as anti‐obesity agents that could lead to body composition improvements in animal or in vivo models ( Charradi et al, ; Moreno et al, ; Park, Park, & Cha, ) . Little is known about the effects of GSE supplementation on food intake and appetite in human (Hendrickson & Mattes, ; Shin et al, ; Vogels, Nijs, & Westerterp‐Plantenga, ). Furthermore, the potential anti‐obesity mechanism of GSE still remains unknown (Jeong, Jung, Cho, Youn, & Hong, ; Vogels et al, ).…”
Section: Introductionmentioning
confidence: 99%